International Trade Statistics Yearbook 2021, Volume I - United Nations Department of Economic; Social Affairs (United Nations, 2022)
The 2021 International Trade Statistics Yearbook, Volume I —Trade by Country — provides a condensed and integrated analytical view of the international merchandise trade, and trade in services up to the year 2021 by means of brief descriptive text, concise data tables and charts. The information presented in the publication give an insight into the latest trends of trade in goods and services of around 175 countries (and areas) in the world. The yearbook is also made available online at https://comtrade.un.org/pb/. For more detailed data, users are requested to go to UN Comtrade (http://comtrade.un.org) which is the source of the information presented in the Yearbook, and is continuously updated. The publication is aimed at both specialist trade data users and common audience at large. The presented data, charts and analyses will benefit policy makers, government agencies, non-government organizations, civil society organizations, journalists, academics, researchers, students, businesses and anyone who is interested in trade issues. The information and analyses are presented in a way which can be comprehended by non-expert users of statistics.